BIOMASS AND NUTRIENTS IN THE FOREST-FLOOR LITTER OF SECOND-GROWTH BRAZILIAN ATLANTIC FORESTS - Marques, Renato; Larsen, Janaina Gabriela; Cattarin, Anadia; de Medeiros Silveira, Fabiana (Floresta, 2023)
This study aimed to evaluate the biomass and chemical composition of the forest floor litter in three remnants of Submontane Dense Ombrophilous Forest located in the Guaricica Natural Reserve in the municipality of Antonina, state of Paraná, Brazil. The areas selected for this study are at different stages of secondary succession, here named initial stage (INI), intermediate stage (INT), and advanced stage (ADV). The litter was collected in different seasons of the year (summer and winter of 2013 and 2014) and sorted into fractions: whole leaves (WL), leaves under some stage of decomposition (DL), miscellaneous litter (ML), and branches (B). After sorting, the litter was oven-dried, weighed, and had the contents of C, N, P, K, Ca, and Mg measured. After that, the accumulated amount of each nutrient in the different litter fractions was estimated. Accumulation of biomass in the INI was lower than that in the ADV. The DL fraction showed the highest level of biomass accumulation among all fractions. The average concentration of macronutrients in the litter showed the following sequence: C>N>Ca>Mg>K>P. The C/N ratio was higher in the INI and INT compared with that in the ADV. Higher levels of macronutrients were frequently observed in the ADV. Inputs of C and of most nutrients increased from the INI to the ADV, except for Ca, whose input varied little throughout the different successional stages.